Foraging across the life span: is there a reduction in exploration with aging? - Mata, Rui; Wilke, Andreas; Czienskowski, Uwe (Frontiers in Neuroscience, 2013)
Does foraging change across the life span, and in particular, with aging? We report data from two foraging tasks used to investigate age differences in search in external environments as well as internal search in memory. Overall, the evidence suggests that foraging behavior may undergo significant changes across the life span across internal and external search. In particular, we find evidence of a trend towards reduced exploration with increased age. We discuss these findings in light of theories that postulate a link between aging and reductions in novelty seeking and exploratory behavior.